Profiling oral health status, values, and related quality of life in patients with oral cancer: a pilot study - Rodrigues, Inês; Botelho, João; Machado, Vanessa; Proença, Luís; Mendes, José João; Zagalo, Carlos (Frontiers in Oral Health, 2023)
Patients diagnosed with oral cancer frequently exhibit an increased likelihood of experiencing common dental conditions, lower dental health literacy, and a decline in their overall quality of life. However, there is limited understanding on the impact of oral health values on these patients. This study aims to explore the oral health status and their oral health determinants and reported outcomes in patients with oral squamous cell carcinoma (OSCC) at the Instituto Português de Oncologia de Lisboa Francisco Gentil. This cross-sectional study included patients who were diagnosed with OSCC for the first time. These individuals were administered a questionnaire that collected sociodemographic data, as well as their scores on the oral health value scale (OHVS) and the short-form oral health impact profile. In addition, participants self-reported their experiences with periodontitis and caries using the decayed, missing, filled index. The final sample consisted of 46 OSCC patients, consisting of 34 males and 12 females. The average age of the participants was 70.0 years (±13.2), with most of them being retired (65.2%). There were no differences found between sex regarding age (p = 0.531), employment status (p = 0.114), presence of systemic conditions, smoking habits (p = 0.423), or alcohol consumption (p = 0.404). In the OHVS, there was a statistically significant difference between men and women regarding the retention of natural teeth (p = 0.021). Patients with self-perceived periodontitis exhibited worse functional limitation (p = 0.039) and physical pain (p = 0.049). Regarding dental caries experience, it was observed that a majority of patients had a higher incidence of missing posterior teeth (59.2%). This sample presented a significant decline in oral health, in addition to the diagnosed OSCC. The oral health value and quality of life were severely declined. There is a concerning lack of oral care and health that, consequently, impacts the quality of life of these patients.